Sosialisasi Gema Cermat (Gerakan Masyarakat Cerdas Menggunakan Obat) dengan Memasyarakatkan “Tanya 5 O” - Fitria Megawati; Ni Putu Dewi Agustini; I Putu Tangkas Suwantara; Ni Putu Udayana Antari; Gusti Ayu Putu Laksmi Puspa Sari (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Public knowledge of self-medication is crucial, and one of the challenges faced is the lack of awareness regarding this practice. Irrational self-medication can lead to harmful consequences, such as incorrect treatment due to inaccurate self-diagnosis. Contributing factors include biased drug advertisements in the media and inadequate information from healthcare professionals. Community engagement is one of the collaborative sharing programs initiated by the Government, known as the Gema Cermat (Smart Community Using Medicines Movement), which includes the promotion tagline "Ask 5 O." This community engagement program aims to enhance the independence of the public in selecting, obtaining, using, storing, and disposing of drugs appropriately, thus promoting rational drug use within society. The target audience for this program was the teenage group of Sekaa Teruna Teruni Panji Semerang in Banjar Sembung Meranggi, Sembung Gede Village, Bali. The results of this community engagement program demonstrated a significant change in participants' knowledge, as assessed through pre- and post-survey questionnaires analyzed using paired T-Test, showing a p-value of 0.000 < 0.005. The findings highlight the beneficial impact of the Gema Cermat program in improving participants' knowledge. Going forward, it is recommended to conduct more frequent community engagement activities across various segments of society to support rational drug use.